USAGE SPHERE OF HYPOPHORA - JAVID BABAYEV (Reviews of Modern Science, 2023)
The article elaborates the sphere of usage of hypohora. It has been noted that hypophora is a rhetorical device where the speaker asks a question and then replies it. It differs from rhetorical question in one aspect. The speaker or writer asks a question and anticipates an answer from the listener or reader while the author himself answers the asked question in hypophora. Hypophoras are found in literature and in the speeches of famous people during the elections. These celebrities can be presidents, prime ministers, TV reporters, journalists, singers and politicians. Ordinary people may also use hypophora in everyday speech. Generally, hypophoras are encountered both in prose and poetry.